CADMIUM REMOVAL BY A BIOREDUCPIUN CORAL BACTERIUM Pseudoalteromonas sp. STRAIN CD15 ISOLATED FROM THE TISSUE OF CORAL Goniastrea aspera, JEPARA WATERS - Agus Sabdono (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Seventeen strains of bacterial symbionts which are resistant to heavy metals, were isolated from the tissue of coral Goniastrea aspera, from Awur Bay, Jepara Waters. Screening procedures involving solid and liquid synthetic media containing Cd2+, resulted in the selection of seven Cd resistant strains, which showed a quantitative removal of Cd2+  by range of 68-90% of the initial Cd2+  concentrations (5 ppm) tested. One of these strains, CD15, was selected further to examine its molecular and physiological characteristics. Based on 16S ribosomal DNA sequencing and microbial characterization, the CG15 isolate is closely related to Pseudoalteromonas sp. This is the first report on the natural Cd metal tolerance levels of coral bacteria